2010
DOI: 10.1038/nn.2494
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal control of stimulated food intake by the endocannabinoid system

Abstract: Activation of cannabinoid type-1 receptors (CB(1)) is universally recognized as a powerful endogenous orexigenic signal, but the detailed underlying neuronal mechanisms are not fully understood. Using combined genetic and pharmacological approaches in mice, we found that ventral striatal CB(1) receptors exerted a hypophagic action through inhibition of GABAergic transmission. Conversely, brain CB(1) receptors modulating excitatory transmission mediated the well-known orexigenic effects of cannabinoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
279
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 261 publications
(307 citation statements)
references
References 15 publications
22
279
4
2
Order By: Relevance
“…The size of this pool of glutamatergicterminal CB 1 receptor molecules seems to be much smaller than that of GABAergic-terminal CB 1 receptors (4, 5). However, CB 1 receptors located on glutamatergic terminals are strongly coupled to heterotrimeric G protein signaling (25) and, in fact, participate in the control of important neurobiological processes such as neuronal excitability (22), motor activity (26), feeding behavior (27), and anxiety (28). Our present findings support that this specific pool of CB 1 receptors should be considered a new key player in the excitotoxicity hypothesis of neural disease (29,30).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The size of this pool of glutamatergicterminal CB 1 receptor molecules seems to be much smaller than that of GABAergic-terminal CB 1 receptors (4, 5). However, CB 1 receptors located on glutamatergic terminals are strongly coupled to heterotrimeric G protein signaling (25) and, in fact, participate in the control of important neurobiological processes such as neuronal excitability (22), motor activity (26), feeding behavior (27), and anxiety (28). Our present findings support that this specific pool of CB 1 receptors should be considered a new key player in the excitotoxicity hypothesis of neural disease (29,30).…”
Section: Discussionsupporting
confidence: 65%
“…We used conditional mutant mice, generated by the Cre-lox technology, in which the CB 1 receptor gene is primarily absent from cortical glutamatergic neurons of the dorsal telencephalon (CB 1 floxed/floxed;Nex-Cre/+ mice; herein referred to as Glu-CB 1 −/− mice) or from forebrain GABAergic neurons (CB 1 floxed/floxed;Dlx5/6-Cre/+ mice; herein referred to as GABA-CB 1 −/− mice) (26,27). Hemizygous mice transgenic for exon 1 of the human huntingtin gene with an expanded CAG tract (∼160 CAG repeats; R6/2 mice) (37) were purchased from Jackson Laboratory [code B6CBA-Tg(HDexon1)62Gpb/1J].…”
Section: Methodsmentioning
confidence: 99%
“…However, the relation between consumption and behavioral reaction is not directly proportional to the dose, but biphasic effects were observed (Viveros et al, 2005). Cannabinoid activity governs in a bimodal manner not only the regulation of anxiety responses but also various other behaviors, including motivational processing (Maldonado, 2002), feeding behavior (Wiley et al, 2005;Bellocchio et al, 2010), novelty seeking (Lafenêtre et al, 2009), and locomotion and exploration (Genn et al, 2004;Häring et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepant observations might be explained by the distribution of CB1 receptors in the brain. The recent development of cell type-specific genetic modification of CB1 receptor function has provided a powerful tool in understanding the cannabinoid action (Monory et al, 2007;Puighermanal et al, 2009;Bellocchio et al, 2010). Thus, we aimed at combining cannabinoid pharmacology and its effects on anxiety with the use of conditional CB1 receptor mutant mice.…”
Section: Introductionmentioning
confidence: 99%
“…In these brain areas, studies in rodents have shown that either CB1R agonists or pharmacological elevations of eCB levels are associated with overfeeding and enhanced rewarding properties of food intake (Cota et al, 2006). Thus, eCB system has a relevant role in the pathophysiological changes associated Food restriction and synaptic plasticity in rat hippocampus G Talani et al with altered feeding behavior and metabolic disorders (Bellocchio et al, 2010). eCBs exert their regulatory activity through the selective interaction with CB1Rs that are mainly located at presynaptic terminals with the result of inhibiting the release of different neurotransmitters, including glutamate and GABA (Ohno-Shosaku and Kano, 2014;Lovinger, 2007), in both hippocampus (Wilson and Nicoll, 2001;Abush and Akirav, 2010) as well as other brain regions (Di Marzo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%